2021
DOI: 10.3946/kjme.2021.187
|View full text |Cite
|
Sign up to set email alerts
|

How the coronavirus disease 2019 pandemic changed medical education and deans’ perspectives in Korean medical schools

Abstract: This study explored how the Korean Medical Colleges responded to the coronavirus disease 2019 (COVID-19) pandemic and the medical deans' perspectives on what and how these adaptions influence the present and the future of medical education. Methods: An email survey combining short and open-ended questions was distributed to all 40 Korean school deans in May 2020. Thirty-seven deans out of 40 medical schools in Korea (92.5%) participated. Results: Most lectures moved online but students' assessments were delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…Due to the widespread outbreak of the coronavirus disease 2019 (COVID-19), many classroom-based lectures moved online, and medical school clinical clerkships were affected to differing degrees across the world [ 1 ]. While lectures and clerkships were on hold, medical students worldwide sought after their duties and social responsibilities in the midst of this pandemic.…”
Section: Problems We Facedmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the widespread outbreak of the coronavirus disease 2019 (COVID-19), many classroom-based lectures moved online, and medical school clinical clerkships were affected to differing degrees across the world [ 1 ]. While lectures and clerkships were on hold, medical students worldwide sought after their duties and social responsibilities in the midst of this pandemic.…”
Section: Problems We Facedmentioning
confidence: 99%
“…Korea’s early pandemic response led to a relatively brief 3-week average suspension of clinical rotations for the start of the academic year in March 2020, which was shorter than in other parts of the world [ 1 ]. The lack of organized institutional volunteering activities like those seen in other countries may have been due to the rapid resumption of the normal clinical curricula and the absence of national or regional lockdowns.…”
Section: Our Thoughtsmentioning
confidence: 99%
“…Around the world, medical schools have undertaken extensive evaluation efforts [8,10,25,26]. Some of them have developed a regional or even national strategy for evaluating digital teaching [4,5,9,31,32]. In Germany, national institutions for higher education development, such as the Centre for Higher Education (Centrum für Hochschulentwicklung; CHE), the German Centre for Higher Education Research and Science Studies (Deutsches Zentrum für Hochschul-und Wissenschaftsforschung; DZHW) or the Institute for Higher Education Development (Institut für Hochschulentwicklung; HIS), have conducted national surveys on the quality and future of digital teaching at German universities [2,7,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the pandemic affected both the pre-clinical and clinical learning environments. However, with the lockdown restrictions gradually easing, clinical rotations are now being rearranged [ 4 7 ]. Nevertheless, pre-medical students, as part of pre-clinical students, grappled with the online curriculum because of social distancing requirements [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the sudden transition to online learning, medical students were highly accepting of the online format and were generally satisfied with the online course [ 4 , 8 – 10 ]. Several studies reported students’ positive perception of online learning, and pre-clinical students, especially, were reported to appreciate online learning.…”
Section: Introductionmentioning
confidence: 99%